GAME AS AN ELEMENT OF HYGIENE MOTIVATION OF PRE-SCHOOLERS - V.S. Melnyk; L.F. Horzov (Ukrainian Medical Stomatological Academy, 2015)
The aim of our research was to evaluate the effectiveness of a game in teaching the pre-schoolers, and the degree of learning to preserve children`s dental health. Materials and methods. 56 pre-schoolers of the Kindergarten № 6, aged 4-6, took part in our research. During the first stage of research we developed special tests, in which we evaluated initial level of children`s knowledge. Tests contained 20 questions showing knowledge of hygienic oral care and useful and harmful to teeth food. During the second stage a questionnaire for parents to assess their degree of awareness on their children`s hygiene and nutrition was developed. It included 16 questions. While testing children and questioning their parents we were monitoring the dental health of pre-schoolers. During the final stage children "passed the exam". All participants were divided conventionally into two groups (28 people each one) by test results. The first group consisted of children with a lower percentage of correct answers output (73.4%), and the second - with the highest percentage (87.6%). When forming groups we followed to determine the relationship between the level of dental knowledge and dental status. Results of the study. Analyzing the initial level of children`s knowledge it has been found that most children know about the need to brush their teeth, but not everyone understands the importance of brushing teeth after eating. Participants of the first group gave 73.4% correct answers of the initial test, and the second group - 87.6%. The "examination" showed a trend to improve the level of knowledge of the first group: they correctly answered 84.4% of the questions, the second group - 91.3%. Thus, we can say that the game promotes better mastering the learning material by pre-schoolers, their desire to get more appreciation for "examination". The results have showed that a higher level of knowledge corresponds better hygiene and dental status of children. Thus, in the first group, the index of intensity of caries was 3.92 ± 0.89, and the hygienic index (GI) - 0.39 ± 0.05, then the second group indices were respectively 2.0 ± 0.8 and 0.24 ± 0.05. Results of the questioning have showed that adults are not sufficiently aware of the dental health status of their children. Hygienic oral care since the moment of the child dentition has been performed by only 30% of respondents, on average, children began to brush their teeth since 1.5 ± 0.05 with the regularity of 1-2 times a day. Analysis of the frequency and purpose of visiting a dentist have showed that only 60% of parents are turning to preventive examinations. Only 56.8% of parents know about necessity of replacement toothbrushes every 3-4 months. Milk products, fruit and vegetables are present in daily diet of each child. Conclusions. 1. Efficiency of the game in learning preschool children is very high. At first child masters the material emotionally and intellectually. Children remember something that gives great interest and best impression. • The positive trend in the level of children`s knowledge has been monitored: in the first group the initial correct knowledge of children was 73.4%,. The "control" children of the same group answered correctly 84.4% of the questions, in the second group the correct ones were 87.6% and 91.3% of the responses respectively. • The direct dependence of children`s dental health and their knowledge on hygiene and nutrition was founded out. • As parents do not have enough knowledge to preserve dental health of their children, there is a need to increase awareness and motivation of the adults in issues of hygiene education and preserving dental health of their children further. • The results of our study indicate the need for new forms of parents` education.